Encyclopedia of India comprehensive coverage of India into the 21st century (New Delhi Encyclopedia Britannica, 2008)
Includes index
Contents: vol.1. A to C (361p.) - vol.2. D to H (367p.) - vol.3. I to Mira Bai (383p.) - vol.4. Miraj to Shastri (377p.) - vol.5. Shath to Z Index (425p.)
Keywords: Encyclopedias and dictionaries; India -- Encyclopedias